Innovation in Processing Binahong Leaves into Crispy Bina Bite Brownies to Create Small Home Industry Businesses - Sugiman Sugiman; Alip Suroto (An International Journal Tourism and Community Review, 2024)
Indonesia is a country rich in natural resources, many plants can grow well in this country. Plants are very useful for humans, because plants are a source of food and medicine for humans. The development of the era makes herbal plants not only used as medicinal ingredients, but can also be used as food ingredients. Many herbal plants can be used for food ingredients, one of which is the binahong plant ( anredera cordifolia ). Binahong plants grow creeping and easy to grow anywhere . Usually found in people's yards for fences, besides that it can be consumed to increase body immunity by boiling and then drinking. All parts of the binahong plant can be used for medicine. Binahong leaves contain alkaloid compounds, flavonoids, polyphenols, saponins and antarquinones.